INTEGRASI PEMIKIRAN THOMAS SAMUEL KUHN DALAM KEILMUAN ISLAM DI ERA MODERN - Syadzali, Ahmad; Rizky, Ali; Yasin, Muhammad; Pikri, Zainal (Faculty of Ushuluddin and Humanities, 2024)
This research explains the integration of Thomas Samuel Kuhn's thoughts in the development of Islamic scholarship in the modern era. The main focus of this research is to highlight paradigm changes in scientific development and its integration in Islamic scholarship. The aim of this research seeks to apply Kuhn's thinking, namely the concept of scientific revolution in developing Islamic scholarship to be able to produce a valuable contribution and solution to the problems faced by Muslims due to technological developments which have given birth to a new paradigm in Islamic scholarship. This research method is qualitative in nature, prepared using library materials or literature studies. This research provides an overview of the scientific revolution put forward by Kuhn and its integration in the development of Islamic science in the modern era, which from Kuhn's thoughts can be applied in the development of Islamic science with the aim of encouraging Islamic thought regarding anomalies and crises as well as revolutions in Islamic science. which can develop understanding of science and produce solutions in facing Islamic scientific problems resulting from developments in time and technology in the modern era. Keywords: Paradigmi; Islamic Science; Integration.